Survey of ICT and Education in Africa : Mozambique Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Mozambique's economy has grown at a steady pace since the end of 1992, following 16 years of civil war. Its education system has also improved markedly with steady increases in school enrolment, even though the numbers of qualified teachers have not kept pace. Mozambique has also been in the lead in southern Africa in developing a national ICT policy and implementation strategy with dedicated programs such as school net Mozambique and the Mozambican ICT Institute (MICTI), which serve as flagship projects in the use of ICTs to facilitate and support learning and skill development in the country.